Compatibility of Lemongrass Extract with Spodoptera litura Nuclear Polyhedrosis Virus Against Spodoptera litura on Soybean Plants - Nafisatul Afidah; Tutung Hadiastono; Bedjo Bedjo; Fery Abdul Choliq (University of Brawijaya, 2021)
Armyworm (Spodoptera litura) is an important pest that damages the leaves of soybean. SlNPV is one type of pathogen that has potential as a biocontrol agent to control armyworms because it is specific, selective, and effective. This study aimed to investigate the compatibility between the lemongrass and SlNPV in controlling armyworm. The Research was conducted at the Laboratory of Indonesian Legumes and Tuber Crops Research Institute (ILETRI) from February 2016 until April 2016. The study using completely randomized design with 7 treatments and 3 replication with a treatment that consists of control, SlNPV-JTM 97C 1,5 × 106 PIB/ml, 10% of lemongrass extract, a combination SlNPV-JTM 97C fixed concentrate of 1,5 × 106 PIB/ml with 2.5%, 5%, 7.5%, and 10% of lemongrass extract. The results showed that the combination of SlNPV-JTM 97C 1.5 × 106 PIB/ml with 10% lemongrass had the highest level of virulence, with 96% of mortality on larva 100% on the pupa stage, so that the combination of SlNPV and lemongrass extracts was compatible in controlling S.litura.